The mediating role of social connectedness and negative cognitive emotion regulation in the association between problematic Internet use and depression among adolescents - Xu, Jiaqi; Chen, Xia-Can; Chen, Lihua; Luo, Dan; Bao, Wenxin; Yang, Xia; Ran, Junzhe; Xu, Jiajun (Frontiers in Public Health, 2024)
While the relationship between adolescent problematic internet use (PIU) and depression has been extensively researched, few studies have investigated the role and mechanisms of social connectedness in this context. This study aimed to investigate the mediating effect of social connectedness (SC) and cognitive emotion regulation, in the relationship between PIU and depression. We conducted a cross-sectional study among 9,407 adolescents aged 12-18 years in China from September 2022 to March 2023. We employed Young's 20-item internet addiction test (IAT-20), Social Connectedness Scale-Revised (SCS-R), Cognitive Emotion Regulation Scale (CER), and DSM5-level 2 Depression Scale to collect mental health outcomes. Logistic regression was performed to examine the independent association between measured variables and depression. Mediation analysis was performed to estimate the mediating role of social connectedness and cognitive emotion regulation, in the relationship between PIU and depression. We found the rate of PIU was 21.8%. The offline SC (indirect effect: 0.112, 95% CI: 0.104-0.121) and negative CER (nCER) (indirect effect: 00.140, 95% CI: 0.129-0.152) mainly played parallel mediating role in the relation between PIU and depression, as well as on_SC (indirect effect: 0.007, 95% CI: 0.005-0.010). These findings provide a new perspective on how PIU influence associated with depression and highlight the importance of enhancing real-life interpersonal interactions. However, the generalizability of this study's findings to other populations may be constrained by cultural factors.